STRATEGI PEMANFAATAN INSTAGRAM SEBAGAI MEDIA DIGITAL MARKETING DALAM MENINGKATKAN OCCUPANCY HOTEL DIASA PANDEMI COVID-19 DI KABUPATEN BADUNG – BALI - Kadek Kreniawati; Ketut Murdani; Ketut Merta (Jurnal Ilmiah Satyagraha, 2022)
Bali has a tourism center in the Badung area, one of which is the Paragon Resort Hotel. During the COVID-19 pandemic, many hotels experienced a decrease in visitors, therefore various promotional tips were carried out by hotel management, one of which was using Instagram. This study aims to determine how much influence Instagram as a digital marketing media has on increasing hotel occupancy during the COVID-19 pandemic in Badung-Bali Regency.In this study, there are two independent variables, namely Digital Marketing (X1), Instagram (X2) and the dependent variable, namely Increasing Hotel Occupancy (Y). The research method used is quantitative research methods and sample collection by convenience sampling method. Data was collected through the distribution of online questionnaires via google form to 100 respondents. The data processing technique was carried out by descriptive analysis through research instrument testing, classical assumption testing, and hypothesis testing. Through the multiple linear analysis test the results obtained on the Instagram variable (X1) have an effect of 0.394 while the Digital marketing variable (X2) has an influence of 0.576 on hotel occupancy (Y). In addition, from the results of the coefficient of determination test, there are results of .478, which means that the influence of the independent variable (X) on the dependent variable (Y) has a very large influence, namely 47.8%. The t-test results show that the significance value is 0.05, which is 0.010 in the X1 variable, while the X2 variable also obtains a significance value of 0.05, which is 0.000 so that it can be stated that Instagram and digital marketing media have a significant effect on increasing hotel occupancy ( Y). In the F test there is a calculated F result that is 44,452 and a significance of 0.000 0.05, this means that there is a simultaneous effect of Instagram (x1) and digital marketing media (x2) on increasing hotel occupancy (Y)